1917 Cal. Stat. 221, § 2 - (:unkn) unknown (My University, 1917)
Prohibited the possession of any instrument or weapon of the kind commonly known as a blackjack, slungshot, billy, sandclub, sandbag, bludgeon, metal knuckles, bomb, or bombshells, and the carrying of any dirk or dagger.
Keywords: POSSESSION - NON-GUN ARMS